2018
DOI: 10.1051/matecconf/201819901005
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of chloride ingress in concrete based on benchmarking field results

Abstract: Modelling the ingress of chloride ions into the cover of a concrete structure is a phenomenon that is gaining an increasing attention of the research community, but even more, from the engineering practice. As the mechanism that drives the ingress of chlorides is implicitly responsible for the service-life of concrete structures, its input parameters are a major issue whenever predicting the service-life of new concrete structures. In this paper most relevant parameters involved in the evaluation of chloride i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In several case studies it has been concluded that the use of a (more) advanced model generally does not necessarily result in a better (or less worse) prediction of chloride ingress in the concrete cover. In [7] a benchmark has been performed based on measured chloride profiles from existing structures, however, the chloride profiles predicted at a later age demonstrate the significant variable outcome between the ingress models used by the respective developers.…”
Section: Deterioration Modelsmentioning
confidence: 99%
“…In several case studies it has been concluded that the use of a (more) advanced model generally does not necessarily result in a better (or less worse) prediction of chloride ingress in the concrete cover. In [7] a benchmark has been performed based on measured chloride profiles from existing structures, however, the chloride profiles predicted at a later age demonstrate the significant variable outcome between the ingress models used by the respective developers.…”
Section: Deterioration Modelsmentioning
confidence: 99%